The Impact of Periodontal Disease on the Quality of Life of People in Timor-Leste measured by the OHIP-TL 24 - Daniel da Costa Pinto; Mutiara Dewi Pangaribuan; Sondang Pintauli (Dentika: Dental Journal, 2025)
Oral health plays an essential role in overall well-being, with periodontal disease being the second most common condition after dental caries. Several studies have shown that the condition significantly affects physical, psychological, and social aspects of life. Therefore, this study aims to evaluate the impact of periodontal disease on quality of life using the Oral Health Impact Profile Timor-Leste version (OHIP-TL 24). An analytical cross-sectional design was used with 150 randomly selected respondents, divided into 3 age groups. These included adolescents (15–19 years), adults (35–44 years), and the elderly (>65 years), with 30 individuals in each group. Periodontal status was assessed using the CPITN index (WHO), and quality of life was measured through the OHIP-TL 24 questionnaire. Data were then analyzed using the Spearman’s rho test. The results showed that the mean CPI score was 1.074 ± 0.56, with the highest treatment needs found in category TN II. Treatment needs were identified in 74% of adolescents, 64% of adults, and 86% of the elderly. The results also showed a significant correlation (p < 0.05) between periodontal disease and decreased quality of life, particularly in the 35–44 age group. In conclusion, periodontal status tends to deteriorate and negatively impact quality of life, showing the need for context-specific oral health interventions in Timor-Leste. Keywords: Dental caries; periodontal disease; periodontal index; quality of life; OHIPTL-24